Diagnostics of Coronal Bright Points using IRIS, AIA, and HMI Observations - Kayshap P.; Dwivedi B.N. (My University, 2025)
We perform the detailed imaging and spectroscopic analysis of two coronal bright points (CBPs). These CBPs are dominated by bright dots or elongated bright features. Their rapid temporal variations lead to a continuous change in their overall morphology at chromospheric and transition-region (TR) temperatures. A 3D potential magnetic field extrapolation predicts the dominance of magnetic loops in the extent of both CBPs, which are clearly visible at the Si iv 1393.75 Å line formation temperature. Short, low-lying magnetic loops or loop segments are the integral parts of these CBPs at TR temperature. A correlation between the various parameters of Mg ii resonance lines (e.g. intensity, Doppler velocity, velocity gradient) is present in the region of magnetic loops or loop segments. However, a quiet-Sun (QS) region does not show any correlation. Doppler velocities as well as the full width at half maximum (FWHM) of these lines are very prominent in the magnetic loops and loop segments compared to the Doppler velocities and FWHM in the QS region. Higher red-shifts and FWHM at TR temperatures are directly related to the dominance of the energy release process in these regions in the framework of the nanoflare model. A magnetogram from the HelioseismicandMagnetic Imager (HMI) onboard the Solar Dynamics Observatory (SDO) reveals the existence of two opposite magnetic polarities in the extent of both CBPs, which is a very well established result. We find that one CBP is formed by the convergence of two opposite magnetic polarities, while the other is triggered by the emergence of a new magnetic field prior to the onset of this CBP. © 2017, Springer Science+Business Media B.V.